The Effectiveness of Using Short Story to Improve Students’ Vocabulary Mastery - Heron Beno (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This research aims to find out the effectiveness of using short story to improve students’ vocabulary mastery at the grade X students SMA Kristen Dian Halmahera in the academic year 2018/2019. The design used in this research was true-experimental design. The researcher involves random assignment of participants into two groups, experimental and control. Both groups are administered both a pretest and a posttest, but the treatment is provided only to experimental group. The researcher conducted this research from January until March 2018 in SMA Kristen Dian Halmahera. The subject was all of the students in X grade. The researcher divided into two classes. Each class consists of 20 students. In collecting the data, the researcher use test. The tests were given in pre-test, and post-test. The researcher analyzed the mean score of each test to find out the improvement of students‟ vocabulary mastery. The researcher conducted the action the students‟ vocabulary mastery increased optimally. It could be seen from the category of test in control class and experimental class. The category of pretest control class students’ score was 6, 65. The category posttest control class students’ score was 7, 65. While the category of pretest experimental class students’ score was 6, 15 and the category of posttest experimental class students' score was 8, 45. After applying the action the researcher was able to improve the students’ vocabulary mastery. The students were able to take the word meaning based on the context. By using short story in teaching vocabulary, students could easily understand and memorize new vocabulary.